Anthropometric characteristics and wingate test parameters of adolescent female football players and track and field athletes - Iveta Bonova; Bozhiya Noeva (Journal of Applied Sports Sciences)
Anthropometric characteristics and anaerobic fi tness are recognized as key factors for successful sports performance. Data thereof are used for more thorough analysis and a better understanding of the results of sports performance. However, the needed data regarding adolescent girls in many sports are still scarce or absent. The aim of this study was to make a comparative assessment of the anthropometric parameters and the characteristics of the anaerobic fi tness of 15-year-old female football players and track and fi eld athletes. The study included 32 subjects who had competed in national championships in Bulgaria. We used established standards to determine the anthropometric characteristics. To determine the anaerobic power, we applied the Wingate test to assess anaerobic fi tness, which is particularly important for sports such as football and track and fi eld athletics – sprint disciplines. The two groups of studied subjects did not diff er signifi cantly in age and height, but there were statistically signifi cant diff erences between the groups in terms of weight, BMI, and Fat%. The Wingate test results also showed a statistically signifi cant diff erence between the two samples regarding the indicators Relative Peak Power (RPP) (W/kg) and Relative Average Power (RAP) (W/kg). The 15-year-old female football players studied were characterized by height that was higher than average for the age, BMI and Fat% that were average for the age, and average RPP values. The studied 15-year-old female track and fi eld athletes were characterized by height that was average for the age, BMI and Fat% that were low for the age, and high RPP values. This study is the fi rst in Bulgaria to focus on adolescent female football players and track and fi eld athletes.